Effect of Marination and Polyphosphate on Quality Improvement of Spent Layer Meat - Anilkumar M (Department of Livestock Products Technology (Meat Technology Unit), College of Veterinary and Animal Sciences, 1997)
Six spent chicken were slaughtered and cut into suitable size, cut up parts were divided into 8 equal parts, two parts were kept as control and the remaining 6 parts were divided into 2 groups and were dipped in 3 per cent STPP solution for 30 minutes and drained, three marinades were prepared containing either curd, lemon juice or tomato pulp. Samples of each group were marinated and kept at 40 C overnight. Parameters such as pH, water holding capacity, weight after marination, weight after overnight chilling, cooking yield and sensory scores were studied after pressure cooking followed by frying and microwave cooking. In this study, it was observed that marination had a significant effect on pH, water holding capacity, cooking yield and organoleptic qualities. The spent chicken meat treated with tomato pulp marinade had the highest score for pH, water holding capacity, cooking yield and organoleptic qualities.